Prevalence and Predictors of Externalizing Behavior in Young Adult Survivors of Pediatric Traumatic Brain Injury. Issue 2 (March 2015) - Ryan, Nicholas P.; Hughes, Nathan; Godfrey, Celia; Rosema, Stefanie; Catroppa, Cathy; Anderson, Vicki A.
Abstract : Objectives: To investigate rates of clinically significant externalizing behavior (EB) in young adult survivors of pediatric traumatic brain injury (TBI) and evaluate the contribution of pre- and postinjury risk and resilience factors to EB outcomes 16 years after injury. Setting: Melbourne, Australia. Participants: Fifty-five young adults (mean age = 23.85 years; injury age: 1.0-12 years) admitted to an emergency department following TBI between 1993 and 1997. Design: Longitudinal prospective study with data collected at the acute, 10-year, and 16-year postinjury time points. Main Measures: Severity of TBI, adaptive functioning, family functioning, full-scale IQ, executive functioning, social communication, and symptoms of EB. Results: One of every 4 young people with a history of pediatric TBI demonstrated clinical or subthreshold levels of EB in young adulthood. More frequent EB was associated with poorer preinjury adaptive functioning, lower full-scale IQ, and more frequent pragmatic communication difficulty. Conclusion: Pediatric TBI is associated with an elevated risk for externalizing disorders in the transition to adulthood. Results underscore the need for screening and assessment of TBI among young offenders and suggest that early and long-term targeted interventions may be required to address risk factors for EB in children and young people with TBI.